1994
DOI: 10.1021/ic00092a025
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of a Trinuclear Complex of Platinum(II) Containing Bridging 1-Methylcytosine Ligands. A Combined X-ray and Multinuclear NMR Study

Abstract: The dinuclear complexes cis-[(PMe3)2Pt(1-MeCy(-H))]2X2 (X = NO3- (1A), ClO4- (1B)), containing NH2-deprotonated 1-methylcytosine (1-MeCy(-H)) ligands, in aqueous or DMSO solution, at 80-degrees-C convert quantitatively into the corresponding trinuclear derivatives cis-[(PMe3)2Pt(1-MeCy(-H))]3X3(2A,B) which have been characterized in the solid state by single-crystal X-ray analysis and in solution by multinuclear (H-1, P-31, Pt-195, C-13, and N-15) NMR spectroscopy. The nitrate salt (2A) crystallizes from eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 0 publications
4
35
0
1
Order By: Relevance
“…At 70°C, in a few days, it converts quantitatively into the trinuclear species 1 characterized by two AB multiplets, having relative intensities of 2:1, at δ −27.01 ( 1 J PPt = 3126 Hz), 28.31 (3234 Hz) at δ −27.14 ( 1 J PPt = 3126 Hz), 28.58 (3234 Hz, with 2 J PP =24.8 Hz) ppm, respectively. The 31 P NMR parameters of the isolated complex, in DMSO-d 6 , collected in Table 1, are very similar to those of the nucleobase analogous, structurally characterized [18]. The presence of two sets of signals for the nucleoside is in line with the existence of two conformers resulting in the relative orientation, syn and anti, of the ribose groups with respect to the pyrimidinic ring.…”
Section: Cytotoxicity Assayssupporting
confidence: 55%
See 1 more Smart Citation
“…At 70°C, in a few days, it converts quantitatively into the trinuclear species 1 characterized by two AB multiplets, having relative intensities of 2:1, at δ −27.01 ( 1 J PPt = 3126 Hz), 28.31 (3234 Hz) at δ −27.14 ( 1 J PPt = 3126 Hz), 28.58 (3234 Hz, with 2 J PP =24.8 Hz) ppm, respectively. The 31 P NMR parameters of the isolated complex, in DMSO-d 6 , collected in Table 1, are very similar to those of the nucleobase analogous, structurally characterized [18]. The presence of two sets of signals for the nucleoside is in line with the existence of two conformers resulting in the relative orientation, syn and anti, of the ribose groups with respect to the pyrimidinic ring.…”
Section: Cytotoxicity Assayssupporting
confidence: 55%
“…In this field we have shown that the neutral ligands in the cisplatin analogs cis-Pt (PR 3 ) 2 Cl 2 (PR 3 = phosphines and diphosphines) play an important role in the nuclearity and reactivity of the platinum-nucleobase adducts. As an example, the reaction of the hydroxo complex cis-[L 2 Pt(μ-OH)] 2 (NO 3 ) 2 with 1-methylcytosine (1-MeCy) causes the deprotonation of the nucleobase leading to cis-[L 2 Pt{μ-1-MeCy(−H),N 3 ,N 4 }] 3 (NO 3 ) 3 when L is PMe 3 [18] and to the mononuclear complex cis-[L 2 Pt{1-MeCy(−H),N 4 } (1-MeCy,N 3 )]NO 3 with L = PPh 3 [19]. In addition, the trinuclear species is stable in solution of nitriles (MeCN, PhCN), whereas the mononuclear species reacts with the solvent to give the amidine derivatives cis-[(PPh 3 ) 2 PtNH=C(R){1-MeCy(−2H)}]NO 3 (R=Me, Ph) [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the crystal structures of several other cyclic nucleobase-containing Pt(II) complexes have been obtained, for example [Pt(en)(uracilate)] 4 (NO 3 ) 4 , which has been shown to weakly bind anions as guests in aqueous solution 13,20 and Pt(II) trimers containing bridging 1-methylcytosine 21,22 or 9-methyladenine. 23 The structure of the cyclic hexamer [(PMe 3 ) 2 Pt(9-methylguanine)] 6 (NO 3 ) 6 · 18H 2 O has been found to have S 3 symmetry with the 9-methylguanines located alternately above and below the plane of the six Pt(II).…”
Section: Introductionmentioning
confidence: 99%
“…Applying them with cisconfigured platinum(ii) and palladium(ii) complexes as metal building blocks this approach leads to multinuclear complex compounds. [6,7] The metals' square-planar coordination spheres are completed by ligands, such as ethylenediamine or cis-arranged phosphanes. In the known platinum and palladium macrocycles, aromatic amine ligands are utilized very rarely.…”
mentioning
confidence: 99%